French Red Cross Ladies in International or Universal Exhibitions (1867–1937) - Belliard, Corinne M. (Frontiers in Sociology, 2019)
This paper attempts to pinpoint what French Red-Cross women were doing in the international exhibitions from 1867 to 1937. They engaged their energies into organizing meetings, exhibitions, and into healing, receiving awards for their work. In spite of their dual activity of exhibitors and healthcarers, they had no specific pavilion at the world fairs. They hovered between the worlds of politics and medicine as distinguished guests but without their own space.